Long-term results of vagal nerve stimulation for adults with medication-resistant epilepsy who have been on unchanged antiepileptic medication - García-Navarrete, Eduardo; Torres, Cristina V.; Gallego, Isabel; Navas, Marta; Pastor, Jesús; Sola, R.G. (Seizure (London, England), 2013)
Several studies suggest that vagal nerve stimulation (VNS) is an effective treatment for medication-resistant epileptic patients, although patients’ medication was usually modified during the assessment period. The purpose of this prospective study was to evaluate the long-term effects of VNS, at 18 months of follow-up, on epileptic patients who have been on unchanged antiepileptic medication. Forty-three patients underwent a complete epilepsy preoperative evaluation protocol, and were selected for VNS implantation. After surgery, patients were evaluated on a monthly basis, increasing stimulation 0.25mA at each visit, up to 2.5mA. Medication was unchanged for at least 18 months since the stimulation was started. The outcome was analysed in relation to patients’ clinical features, stimulation parameters, epilepsy type, magnetic resonance imaging (MRI) results, and history of prior brain surgery. Of the 43 operated patients, 63% had a similar or greater than 50% reduction in their seizure frequency. Differences in the responder rate according to stimulation intensity, age at onset of epilepsy, duration of epilepsy before surgery, previous epilepsy surgery and seizure type, did not reach statistical significance. Most side effects were well tolerated. 62.8% of our series of 43 medication-resistant epileptic patients experienced a significant long-term seizure reduction after VNS, even in a situation of on unchanged medical therapy. Patient characteristics predictive of VNS responsiveness remain subject to investigation. Controlled studies with larger sample sizes, on VNS for patients with medication-resistant epilepsy on unchanged medication, are necessary to confirm VNS efficacy for drug-resistant epilepsy, and to identify predictive factors.